Complete genome sequencing of exopolysaccharide-producing Lactobacillus plantarum K25 provides genetic evidence for the probiotic functionality and cold endurance capacity of the strain. Issue 7 (3rd July 2018) - Jiang, Yunyun; Zhang, Jian; Zhao, Xiao; Zhao, Wen; Yu, Zhijian; Chen, Chao; Yang, Zhennai
Abstract: Lactobacillus plantarum ( L. plantarum ) K25 is a probiotic strain isolated from Tibetan kefir. Previous studies showed that this exopolysaccharide (EPS)-producing strain was antimicrobial active and cold tolerant. These functional traits were evidenced by complete genome sequencing of strain K25 with a circular 3, 175, 846-bp chromosome and six circular plasmids, encoding 3365 CDSs, 16 rRNA genes and 70 tRNA genes. Genomic analysis of L. plantarum K25 illustrates that this strain contains the previous reported mechanisms of probiotic functionality and cold tolerance, involving plantaricins, lysozyme, bile salt hydrolase, chaperone proteins, osmoprotectant, oxidoreductase, EPSs and terpenes. Interestingly, strain K25 harbors more genes that function in defense mechanisms, and lipid transport and metabolism, in comparison with other L. plantarum strains reported. The present study demonstrates the comprehensive analysis of genes related to probiotic functionalities of an EPS-producing L. plantarum strain based on whole genome sequencing. Abstract : : Ubiquitous and unique functional genes are the reason why an EPS-producing L. plantarum K25 strain has probiotic functionalities and stresses tolerances based on whole genome sequencing.